PENGEMBANGAN PEMBELAJARAN DENGAN PENDEKATAN STEM TERINTEGRASI SCIENCE ENTREPRENEURSHIP UNTUK MENGEMBANGKAN KARAKTER KEWIRAUSAHAAN (Universitas Negeri Semarang, 2021)
This study aims to determine the characteristics and feasibility of learning media for the integration of the STEM integrated with science entrepreneurship and to analyze the student entrepreneurial character profile in the application of learning tools for integrating the STEM integrated with science entrepreneurship. The learning media development model used is ADDIE. The data were collected by means of observation, questionnaires, and tests. The characteristics of the learning media developed include the integration of the STEM integrated with science entrepreneurship and refer to the indicators of entrepreneurial character developed in students. The research results show that the learning media is very feasible with an average percentage of 96.42%. The entrepreneurial character profile with the application of integrated learning media of the STEM integrated with science entrepreneurship has increased by obtaining a gain of 0.60 in the moderate criteria. Students give good responses on small and large scale trials. This means that learning can develop entrepreneurial character, LKPD and easy to understand questions. Based on the results of the study, it can be concluded that the integrated learning media of the STEM integrated with science entrepreneurship can develop the entrepreneurial character of students because there is an increase in the percentage score of entrepreneurial character on each observation.